EXPERIMENTAL AND SIMULATION STUDIES OF ELECTROMAGNETICALLY ACTIVATED MULTIFERROIC-BASED NANOFLUIDS FOR APPLICATION IN ENHANCED OIL RECOVERY - ALI, HASSAN (2020)

(untitled)
Electromagnetic-assisted nanofluids emerged as a new frontier for enhanced oil recovery (EOR).